Pedagogy course instructor video - Graham, George; Beranich, Kathryn L. ([S.l.] : Human Kinetics, 1993)
It is part of a series of resources and courses designed to improve the teaching of children's physical education
This video companion to the book Teaching children physical education : becoming a master teacher
Narrator: George Graham
Keywords: Physical education for children; Physical education and training; Teaching